2022
DOI: 10.1101/2022.05.26.22275604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cultural Evolution of Vaccine Hesitancy: Modeling the Interaction between Beliefs and Behaviors

Abstract: In the last decade, despite the proven efficacy of vaccines, the developed world has seen a resurgence of vaccine-preventable diseases (VPDs) such as measles, pertussis, and polio. Vaccine hesitancy, an individual behavior influenced by historical, political, and socio-cultural factors, is believed to be a primary factor responsible for decreasing vaccine coverage, thereby increasing the risk and occurrence of VPD outbreaks. Society, culture, and individual motivations affect human decisions regarding health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Here, we build on the cultural niche construction framework proposed by [26] to model the cultural spread of vaccine attitudes and vaccination behavior in the presence of external forces imposed by two scenarios: vaccine mandates and vaccine inaccessibility. Multiple factors influence an individual's vaccine-related beliefs and a couple's decision to vaccinate their offspring, including their own vaccination status and their perception of the relative risks of the disease and the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we build on the cultural niche construction framework proposed by [26] to model the cultural spread of vaccine attitudes and vaccination behavior in the presence of external forces imposed by two scenarios: vaccine mandates and vaccine inaccessibility. Multiple factors influence an individual's vaccine-related beliefs and a couple's decision to vaccinate their offspring, including their own vaccination status and their perception of the relative risks of the disease and the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…With our initial model [26], we showed that when population traits are at or near an equilibrium, we can infer that a population with high vaccination coverage will have low rates of vaccine hesitancy and vice versa. However, when there are external pressures as modeled here, such as increased pressure to vaccinate or difficulty in acquiring vaccination exemptions, an undercurrent of vaccine hesitancy can persist in a relatively well-vaccinated population, potentially limiting the adoption of newly introduced vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations